REFLEKSI PENELITIAN BUDAYA KAIZEN DI INDONESIA - Ramadhani, Isma Aururonnisa; Ikhwan, Khairul (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study was carried out with the intention of providing an overview of the evolution of research or studies on how the culture of kaizen is in Indonesia. Articles that were published in 12 national journals over the course of this study's observation period of six years, from 2016 to 2021, make up the sample for this research. The data obtained consists of 19 different publications that talk about kaizen culture. The method of charting the field was the method that was applied in this study. This study classifies papers according to their subject matter, type of research, and sector or field of research (area). The topic of the most extensively researched dependent variable is employee performance, the topic of the most extensively researched independent variable is organizational culture, and the research method with a quantitative approach is the research method that is employed the most frequently. The majority of study investigating kaizen culture is conducted by commercial companies and organizations.